2022
DOI: 10.7759/cureus.30812
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Glucagon-Like Peptide-1 Receptor Agonists in Patients With Asthma: A Literature Review

Abstract: Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) are approved to treat type 2 diabetes mellitus. The anti-inflammatory and anti-obesity properties of GLP-1 RAs as well as their moderating effects on multiple pathobiological pathways in asthma pathogenesis may decrease asthma exacerbations, improve quality of life, and decrease premature death among patients with asthma and co-morbid diabetes or obesity.The aim of this literature review is to discuss evidence from basic science, human studies, and clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…GLP-1 acts through the activation of G-protein-coupled receptors. GLP-1R and GLP-1R agonists are already approved for type-2 diabetes mellitus (T2DM) and obesity treatment [ 193 ]. The early research has demonstrated that the level of plasma GLP-1 after oral carbohydrate ingestion is considerably decreased in obese patients in comparison to a lean group [ 194 ].…”
Section: Peptides In Asthma–obesity Phenotypementioning
confidence: 99%
See 1 more Smart Citation
“…GLP-1 acts through the activation of G-protein-coupled receptors. GLP-1R and GLP-1R agonists are already approved for type-2 diabetes mellitus (T2DM) and obesity treatment [ 193 ]. The early research has demonstrated that the level of plasma GLP-1 after oral carbohydrate ingestion is considerably decreased in obese patients in comparison to a lean group [ 194 ].…”
Section: Peptides In Asthma–obesity Phenotypementioning
confidence: 99%
“…GLP-1, in addition to participating in glycemic control, has anti-inflammatory properties under many different conditions [ 195 ]. Given the fact that GLP-1R receptors are present in the respiratory tract, including airway smooth muscle cells, pulmonary vasculature, or type-II alveolar cells [ 193 ], GLP-1 may play an important role in the inflammatory processes associated with asthma. In fact, in a murine model of OVA-induced asthma, GLP-1 analog liraglutide significantly reduced airway inflammation, mucus hypersecretion, and elevated levels of E-selectin or MUC5AC mucin [ 196 ], whereas another GLP-1R agonist, exendin-4, showed a bronchorelaxant effect, alleviating hyperresponsiveness of human isolated bronchi subjected to passive sensitization and high-glucose concentration [ 197 ].…”
Section: Peptides In Asthma–obesity Phenotypementioning
confidence: 99%